The Role of Vitamin D in Metabolic Syndrome in Polycystic Ovary Syndrome - Intisar Younis Mohammed Ibrahim (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objective: The aim of this study was to assess the women complaining from polycystic ovary syndromeand the relation of serum vitamin D levels according to the different phenotypes of the disease by aretrospective study.Methods: Records for 242 infertile women diagnosed with PCOS have been examined. In thisretrospective study, 100 of them have been randomly recorded for 4 PCOS phenotypes. 40 normalovulation women with a male factor history were selected as the control group.In four phenotype types including: age, BMIs, the infertility duration, the hormonal profile and theserum vitamin D, the P value of 0.05 was found to be statistically significant.Results: In comparison with PCOS patients (P<0.001), the data showed a serum vitamin D level ofstatistically importance in the control group. Also, four PCOS phenotypes had no significant variation inthe serum vitamin D levels.Conclusions: There were no significant differences between the serum vitamin D levels of the differentPCOS phenotypes. The additional studies of large samples are recommended for determining the roleof the serum vitamin D level in PCOS patients.